Playing video games as a distraction can reduce anxiety in children before circumcision - Sutrisno; Herawati, Vitri Dyah (JOURNAL OF Mental Health Concerns, 2026)
Background: Circumcision is a minor surgical procedure that aims to cut and clean the prepuce of the penis for various indications. This minor surgical procedure causes varying degrees of anxiety in most children. One intervention to reduce anxiety in children before circumcision is to distract them with video games. Purpose: To determine the effect of playing video games on anxiety in children undergoing circumcision. Method: A pre-experimental study with a one-group pre-test post-test design. The sample size was 32 children selected based on several criteria: no visual or hearing problems, cooperative patients, no excessive anxiety, and good communication skills. The Child Anxiety Scale was used to assess anxiety. Statistical analysis used the Wilcoxon rank sum test. Results: The level of anxiety in children before circumcision was mostly in the moderate anxiety range before the intervention, with 14 (43.8%) having an average score of 2.25. After the video game intervention, 14 (43.8%) children experienced mild anxiety with an average score of 1.01. The Wilcoxone rank sum test yielded a p-value of 0.001 (p < 0.05). Conclusion: Playing video games can reduce anxiety levels in children prior to circumcision. Keywords: Anxiety; Circumcision; Playing; Video Games.